Migration and its health and social problems in the Czech Republic. Part II - Nesvadbová, L; Rutsch, J; Sojka, S (Central European journal of public health, 1997)
The study follows a theoretical introduction. It tries to analyze the health and social situation of three groups of migrants: mostly ukrainian citizens, who work with Czech firms. We try to evaluate chosen methodology for further use in longitudinal following of similar groups of foreigners, who are working with Czech firms (under international contract). Our aim is to develop a general strategy for the care of migrants.
Keywords: dospělí; Research Design; Female; Adult; ženské pohlaví; longitudinální studie; Ukrajina; zdravotnické plánování; Health Services Needs and Demand; Health Status; lidé; zdravotní stav; surveillance populace; Ukraine; Social Problems; emigrace a imigrace; Middle Aged; Health Planning; Male; zdravotnické služby - potřeby a požadavky; Czech Republic; sociální problémy; Population Surveillance; Česká republika; lidé středního věku; mužské pohlaví; Emigration and Immigration; výzkumný projekt; Longitudinal Studies; Humans